Attenuation of Bessel vortex beam transmission in the rain environment. (August 2023) - Dong, Kangjun; Jiang, Wenjie; Cheng, Mingjian; Shi, Chenge; Cao, Yuancong; Guo, Lixin
Highlights: Single scattering model of single Mie scattering model of the raindrop particles under incident Bessel beams is established. Energy attenuation characteristics of high-order Bessel beams transmission in rainfall atmospheric medium are simulated. Penetration ability of high order Bessel vortex beam in rainfall environment is significantly stronger than that of non-vortex beam. Abstract: Vortex beam propagates in the atmospheric environment, it interacts with the floating cloud, fog, rain and other micro particles, the absorption and scattering effects will lead to the energy attenuation of vortex beam, and result in the degradation of the transmission quality of vortex beam signal. Single scattering between Bessel vortex beam and raindrop particles is simulated based on generalized Lorentz Mie theory. Combined with the raindrop particle size distribution model, the transmission and attenuation characteristics of Bessel vortex beam in rainfall environment are analyzed. Bessel vortex beam with orbital angular momentum (OAM) has multiring intensity structure and spiral phase distribution, and the extinction efficiency factor of Bessel vortex beam caused by raindrop absorption and scattering in rainfall environment is smaller than that of Gaussian beam. Bessel vortex beam has the weaker energy attenuation in rainfall, and has stronger penetration ability of rain and fog. With the increase of topological charge, the extinction efficiency factor and energy attenuation rate caused by raindrop absorption and scattering further decrease. Bessel vortex laser with larger topological charge and bigger axial cone angle has stronger penetrating ability in rainfall environment.